The mediating role of leader–member exchange: a study of job satisfaction and turnover intentions in temporary work. (28th January 2016) - Flickinger, Miriam; Allscher, Marcel; Fiedler, Marina
Abstract: This paper focuses on turnover intentions in temporary work. Specifically, we analyse whether job satisfaction and leader–member exchange (LMX) play the same role as antecedents of turnover intentions for both temporary and permanent employees. Results from a total‐effects moderation model based on a survey of 593 individuals placed by a temporary work agency suggest that temporary work lessens the impact that high job satisfaction has in terms of reducing turnover intentions. Furthermore, while for permanent employees, high‐quality LMX relationships play a central role in the link between job satisfaction and turnover intentions; for temporary employees, job satisfaction is less important in the formation of high‐quality LMX relationships. Therefore, we contribute to knowledge on turnover intentions in temporary work by showing that within this context, turnover intentions cannot be directly remedied by high job satisfaction and that temporary work inhibits LMX's reinforcing role in the relationship between job satisfaction and turnover intentions.